KEPEMIMPINAN KEPALA SEKOLAH BERBASIS ASAH, ASIH, ASUH DALAM MENINGKATKAN LITERASI DIGITAL GURU DI GUGUS PAUD PANJATAN - Eti Pratiwi; Agustin Sri Purnami; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study is to analyze the Leadership of Principals Based on Asah, Asih, Fostering in Increasing Teacher Digital Literacy, to analyze the obstacles encountered in the Strategy of Principals Based on Asah, Asih, Fostering in Increasing Teacher Digital Literacy, and to analyze the effectiveness of the Strategy of Asah-Based Principals, Love, Foster in Improving Teacher Digital Literacy. While this research uses a descriptive qualitative approach that serves as a way to understand and discover central phenomena, qualitative research can be used to understand and interpret people's experiences. The research subject is the party that the researcher wants to examine, namely the party that is the main target in a study. The subjects in this study were supervisors, school principals, all teachers, at Kusuma Mekar I Kindergarten, ABA Bugel Kindergarten, ABA Dukuh Kindergarten, Panjatan District. Data was collected using interview, observation, and documentation techniques. Data were analyzed using qualitative analysis. The results of the study show that leadership efforts based on the principles of compassion, care, and care in improving teacher digital literacy are planning digital literacy training for teachers, planning how teachers feel safe and comfortable to take part in digital literacy training, and planning to make an official order from the head of PAUD to participate. training that can be used as a sign that digital literacy training activities that teachers participate in are official and legal activities. Organizing is done by organizing digital literacy training so that it is carried out alternately by PAUD teachers so they don't have to close schools, organizing teachers so they can take part in training without teaching, organizing physical support for teachers who take part in training in the form of physical support in order to free teachers from teaching while they are participating. training. Supervision is carried out by supervising that the teacher concerned actually takes part in the training, supervising the teacher assigned to replace teaching actually replaces teaching, supervising that the physical and psychological needs of the teacher conducting the training are actually fulfilled. Evaluation is carried out by comparing the results of digital literacy training, examining the obstacles that occur in teachers replacing other teachers who are participating in digital literacy training, and examining the obstacles that occur when meeting the physical needs of teachers participating in digital literacy training activities. Internal obstacles to leadership based on the principles of compassion, care, and fostering in increasing teacher digital literacy are teachers who are still uncomfortable leaving their classes, and teachers who are reluctant to apply the knowledge they gain from training. External obstacles experienced by leadership based on the principles of compassion, care and fostering in digital literacy of teachers in the PAUD Panjatan cluster were protests from parents because classes had to start in the afternoon and also sudden service. The results of the study show that the effectiveness of leadership based on the principles of compassion, care, fostering digital literacy of teachers in the Panjatan PAUD cluster is seen and assessed from the indicators of the success of the principal in improving teacher literacy skills which is very good. Teaching based on the principles of teaching, caring, fostering digital literacy for teachers in the early childhood education group has been considered effective because teachers have mastered digital literacy skills after implementing leadership based on the principles of teaching, caring, fostering digital literacy for teachers in the early childhood education group. Ability to use digital learning media, ability to create technology and information-based learning media products, ability to create new ideas in carrying out learning, ability to use digital space-based learning media, ability to interpret other people's ideas, ability to communicate using digital technology, ability to understand and understand students , the ability to search for information using digital media, the ability to analyze information obtained from the digital world, the ability to interpret according to the context of socio-cultural understanding, the ability to guarantee the security of personal data when using information and communication technology.